A Novel Prevention Bundle to Reduce Surgical Site Infections in Pediatric Spinal Fusion Patients. (28th January 2016) - Gould, Jane M.; Hennessey, Patricia; Kiernan, Andrea; Safier, Shannon; Herman, Martin
Abstract : BACKGROUND: The Surgical Care Improvement Project bundle emphasizes operative infection prevention practices. Despite implementing the Surgical Care Improvement Project bundle in 2008, spinal fusion surgical site infections (SF-SSI) continued to be prevalent for this low-volume, high-risk surgery. OBJECTIVE: To design a combined pre-, peri-, and postoperative bundle (PPPB) that would lead to sustained reductions in SF-SSI rates. DESIGN: Quality improvement project, before-after trial with cost-effectiveness analysis. SETTING: Children's hospital. PATIENTS: All spinal fusion patients, 2008–2015. INTERVENTION: A multidisciplinary team developed the PPPB composed of Surgical Care Improvement Project elements plus improved wound care practices, nursing standard of care, dedicated nursing unit, dermatology assessment tool and consultation, nursing education tool using "teach back" technique, and a "Back Home" kit. SF-SSI rates were compared before (2008–2010) and after (2011-February 2015) implementation of PPPB. PPPB compliance was monitored. RESULTS: A total of 224 SF surgeries were performed from 2008 to February 2015. Pre-PPPB analysis revealed median time to SF-SSI of 28 days, secondary to skin and bowel flora. Mean 3-year pre-PPPB SF-SSI rate per 100 SF surgeries was 8.2 (8/98) (2008: 13.3 [4/30], 2009: 2.7 [1/37], 2010: 9.7 [3/31]). Mean SF-SSI rate after PPPB was 2.4 (3/126) (January 2011-February 2015); there was a 71% reduction in mean SSI rate ( P =.0695). No SF-SSI occurred in neuromuscular patients ( P =.008) after PPPB. Compliance with PPPB elements has been 100%. CONCLUSIONS: PPPB led to sustained improvement in SF-SSI rates over 50 months. The PPPB could be reproduced for other surgeries. Infect Control Hosp Epidemiol 2016;37:527–534